Roles of autophagy in breast cancer treatment: Target, bystander or benefactor. (November 2020) - Tyutyunyk-Massey, Liliya; Gewirtz, David A.
Abstract: Despite the availability of largely effective treatments for breast cancer, such as the combination of aromatase inhibitors or anti-estrogens with cdk4/6 inhibitors for estrogen receptor positive/Her 2 negative breast cancer, breast cancer remains a significant cause of morbidity and mortality. This is due, in large part, to a very limited understanding of the mechanisms underlying the failure of conventional therapies and disease recurrence after tumor dormancy. One cellular process that is activated in response to the majority of breast cancer treatments is autophagy. Proven to be an indispensable cellular function, autophagy is largely accepted as a pro-survival mechanism in tumor cells and has consequently generated significant interest in cancer research and treatment strategies. Autophagy plays multiple and often disparate roles during different stages of tumorigenesis and in response to anti-tumor treatments; in fact, autophagy is induced by almost all conventional treatments of breast cancer and is considered a target for pharmacologic blockade in the clinic. Consequently, it is important to further our understanding of this process and its role in breast cancer.